Social informatics. 10th International Conference, SocInfo 2018, St. Petersburg, Russia, September 25-28, 2018, Proceedings /: 10th International Conference, SocInfo 2018, St. Petersburg, Russia, September 25-28, 2018, Proceedings. Part II : (2018) - Unknown
No abstract available